The genome sequence of the Thistle Conch moth, Aethes cnicana (Westwood, 1854) [version 1; peer review: 2 approved] - Mark R Young (Wellcome Open Research)
We present a genome assembly from a male specimen of Aethes cnicana (Thistle Conch; Arthropoda; Insecta; Lepidoptera; Tortricidae). The genome sequence has a total length of 412.26 megabases. Most of the assembly (96.09%) is scaffolded into 30 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled, with a length of 15.66 kilobases.